Household transitions to energy efficient lighting - Bradford Mills; Joachim Schleich (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2013)
New energy efficient lighting technologies have the potential to significantly reduce household electricity consumption. But adoption of many technologies has been slow. This paper employs a unique dataset of German households to examine the factors associated with the replacement of old incandescent lamps (ILs) with new energy efficient compact fluorescent lamps (CFLs) and light emitting diodes (LEDs). The 'rebound' effect of increased light luminosity during the transition to energy efficient bulbs is analyzed jointly with the replacement decision to control for household self-selection in bulb-type choice. The results indicate that the EU ban on ILs accelerated the pace of transition to CFLs and LEDs, while storage of bulbs significantly dampened the speed of the transition. Households also appear responsive to new bulb attributes, as those with stated preferences for energy efficient, environmentally friendly, and durable lighting are more likely to replace ILs with CFLs and LEDs. Higher lighting needs generally spur IL replacement with CFLs or LEDs. However, electricity gains from new energy efficient lighting are mitigated by increases in bulb luminosity; with average increases in luminosity of 23% and 47% upon transitioning to CFLs and LEDs, respectively.
Keywords: 330